Studies of gastric mucosa regeneration and safety promoted by Mouriri pusa treatment in acetic acid ulcer model - Vasconcelos, P. C. P. [UNESP]; Kushima, H. [UNESP]; Andreo, M. [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Vilegas, Wagner [UNESP]; Takahira, Regina Kiomi [UNESP]; Pellizzon, C. H. [UNESP] (Elsevier B.V., 2008)
Ethnopharmacological Relevance: Mouriri pusa Gardn. (Melastomataceae) is a medicinal plant commonly used by people living in the Cerrado to treat gastrointestinal disturbances. This medicinal plant has shown intense gastroprotective action in rodent gastric lesion, but still there are no data about its healing effect on gastric mucosa.Aim of the Study: To evaluate the methanolic extract (MeOH) obtained from Mouriri pusa leaves for its effect on the cicatrisation process of gastric ulcer.Mterials and Methods: The healing effects on gastric ulcers inducted by subserosal injection of acetic acid were evaluated by macroscopic and microscopic measures, imunohistochemistry and cell counting in rats treated with MeOH extract of Mouriri pusa (250 mg/kg, p.o./daily) for 14 or 30 days. The toxicity of Mouriri pusa was also evaluated by body and organ weight measure and clinical biochemical parameters.Results: Mouriri pusa treatments lasting 14 and 30 days showed elevated mucus secretion (PAS) and thicker regenerative gastric mucosa, denoting increased cell proliferation, which was confirmed by PCNA immunohistochemical analysis. Moreover, there was important cell recruitment (neutrophils and mast cells) to the site of the ulcer, which is an important factor in ulcer healing. No toxic effect was observed in all parameters evaluated. Phenolic compounds present in the MeOH extract like tannins, flavonoids and epicatechin are the probable agents involved in the healing effects of this medicinal plant.Conclusions: These findings showed a potential effect of Mouriri pusa in increasing regeneration of damaged gastric mucosa with safety for human use. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Mouriri pusa; melastomataceae; healing gastric ulcer; toxicity